Lexical Density: Comparative Analysis of "Amboyo" and "Dayakng Janjola" in Dayak Kanayatn Language - Wanda Giovani (CAKRAWALA LINGUISTA, 2025)
This study analyzes linguistic and cultural transformations in the Dayak Kanayatn community by a quantitative assessment of lexical density. This research posits that an analysis of lexical density can indicate quantifiable changes between traditional and current songs, mirroring broader cultural evolution. The research contrasts two significant musical artifacts: the traditional religious song "Amboyo," integral to the Naik Dango harvest ceremony, and the contemporary popular song "Dayakng Janjola," which embodies modern expression. This study utilizes the methodology proposed by Ure (1971) to calculate lexical density, thereby evaluating the proportion of meaningful (lexical) words relative to the total word count in the lyrics of the two songs.The results demonstrate that "Amboyo" comprises a substantially greater number of words than "Dayakng Janjola." The results indicate a linguistic transformation in Dayak Kanayatn music, shifting from a medium for conveying profound narratives, mythological, and cosmological information to a vehicle for immediate emotional expression, entertainment, and social connectivity. The study indicates that variations in lexical density represent not only a linguistic phenomena but also a quantitative reflection of language evolution, cultural transmission, and identity formation within the contemporary Dayak Kanayatn group.1